Salafiyah Pesantren in Countering Radicalism through Culturally-Based Fiqh Education and Promoting Moderate Islam on Social Media - Muqit, Abd.; Junaidi, Junaidi; Nawafil, Moh. (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
Radicalism in the education sector poses significant challenges for policymakers in Islamic boarding schools (pesantren) to protect students from extremist ideologies. This study examines how Salaf pesantren, through culturally-based fiqh education, instills values of moderation and implements effective teaching methods to counter radical movements. Additionally, this research analyzes the contribution of students in promoting moderate Islam through various social media platforms. Using a qualitative research approach, data were collected through observations and interviews with key stakeholders. The findings reveal that multi-madhhab fiqh studies and the integration of local cultural values are crucial in fostering an understanding of moderate Islam among students. Furthermore, social media platforms are effectively utilized to promote moderate Islam. Teachers employ various teaching methods to transform rigid and difficult-to-understand fiqh material into more flexible and comprehensible content. These strategies demonstrate the resilience of pesantren against radicalization. Pesantren also contribute to the campaign for moderate Islam in this era of globalization through various social media platforms managed by students.